Strategi Kebijakan Digitalisasi Pertanian Berbasis Petani Milenial di Indonesia: Pendekatan Analisis SWOT - Noviar, Helmi; Fadhlain, Said (Universitas Teuku Umar, 2025)
AbstractDigital transformation in the agricultural sector is a strategic response to the challenges of production efficiency, farmer regeneration, and national food security. Millennial farmers, accounting for 21.89% of agricultural enterprises in Indonesia, hold great potential as agents of change due to their openness to technology and adaptive capacity. This study aims to formulate digital agricultural policy strategies based on millennial farmers using the SWOT analysis approach. Data were sourced from the 2023 Agricultural Census and relevant literature and policy documents. A descriptive analysis was conducted using a SWOT matrix and four strategic quadrants (SO, ST, WO, WT). The findings reveal significant challenges in digital literacy, infrastructure limitations, and weak institutional integration. Nonetheless, major opportunities exist through policy support, agritech advancement, and the entrepreneurial interests of young farmers. Recommended strategies include community-based digital training, development of digital cooperatives, farmer data integration, and reform of subsidy systems. In conclusion, millennial farmers serve as a strategic pivot for agricultural digitalization and require integrated, collaborative, and responsive policy interventions across sectors.Keywords: millennial farmers, agricultural digitalization, public policy, SWOT analysis.